Integrasi Indeks Saham Pada Bursa Negara Kawasan Asia Pasifik - I Wayan Tresna Wira Sentana; I Gde Kajeng Baskara (Asosiasi Peneliti Manajemen Adat Indonesia, 2020)
Financial liberalization that occur in many countries in the world will cause stock market in that countries are integrated. Asia Pacific stock markets are very potential for investors to investing their capital because the Asia Pacific stock markets are very potential to make maximum returns for the investors. The aim of this researches are to analyze integration that occur in the Asia Pacific stock markets and to know that Asia Pacific stock markets are suitable for investors to diversifying their portfolio. This research are using the closing price of the Asia Pacific stock markets from April 2011 – March 2019 using Johansen cointegration test and vector error correction model. The result shows that Asia Pacific stock markets are integrated shows with seven cointegrating values in Johansen cointegration test and investors cannot diversifying their portfolio in the Asia Pacific stock market because of positive correlation coefficient values from all of the variables